El consumo de cibermedios en los estudiantes de la Universidad Técnica de Babahoyo en el 2019 - Quiñonez Arañes, Nathaly Silvana (2019)
Research on "The consumption of online media in students from the Technical University of Babahoyo in 2019, aims primarily to determine the level of consumption of those CiberSpaces, in this study the educational and communicative line with the subline was used, art and culture, thus contributing to community development and visibility. The results obtained were based on a survey where it was determined that students consume cybermedia in said institution by 90% and that the type of information they seek in these spaces is entertainment and information